Mobility of Iron-Cyanide Complexes in a Humic Topsoil under Varying Redox Conditions. (4th January 2009) - Rennert, Thilo; Mansfeldt, Tim
Abstract : The potentially toxic Fe-CN complexes ferricyanide, [ Fe III ( CN ) 6 ] 3 −, and ferrocyanide, [ Fe II ( CN ) 6 ] 4 −, undergo a variety of redox processes in soil, which affect their mobility. We carried out microcosm experiments with suspensions of a humic topsoil (pH 5.3;C org 107 gkg - 1 ) to which we added ferricyanide (20 mgl - 1 ). We varied the redox potential (E H ) from −280 to 580 mV by usingO 2, N 2 and glucose. The decrease ofE H led to decreasing concentrations of Fe-CN complexes and partial reductive dissolution of (hydrous) Fe and Mn oxides. The dynamics of aqueous Fe-CN concentrations was characterized by decreasing concentrations when the pH rose and theE H dropped. We attribute these dependencies to adsorption on organic surfaces, for which such a pH/E H behavior has been shown previously. Adsorption was reversible, because when the pH andE H changed into the opposite direction, desorption occurred. This study demonstrates the possible impact of soil organic matter on the fate of Fe-CN complexes in soil.